Near-Infrared Spectroscopy of the Urinary Bladder during Voiding in Men with Lower Urinary Tract Symptoms: A Preliminary Study. (14th July 2013) - Farag, Fawzy F.; Meletiadis, Joseph; Saleem, Mohamad D.; Feitz, Wout F.; Heesakkers, John P.
Abstract : Objectives . To determine the difference in response of NIRS of the bladder during voiding between men with and without BOO.LUTS. Methods . A prospective, case series, study included 36 men with LUTS. Patients completed the IPSS questionnaire; prostate volumes were measured sonographically. Patients underwent pressure flow study (PFS) with simultaneous NIRS of the bladder. Amplitudes of HHb, O2 Hb, and Hb sum were calculated at Q max, relative to baseline. Patients were urodynamically classified as obstructed and unobstructed. Recursive partition analysis (RPA) was performed to reclassify patients using NIRS amplitudes, followed by combined data of NIRS amplitudes, prostate volume, IPSS, and Q max to determine the best predictor(s) of BOO. Results . PFS classified 28 patients as obstructed and 8 as unobstructed. The median HHb amplitude was significantly higher in obstructed group. RPA of NIRS amplitudes correctly reclassified 89% of patients [AUC: 0.91]. RPA of the combined IPSS, prostate volume, PVR, and Q max correctly reclassified 72% of patients [AUC: 0.84]. When NIRS amplitudes were added to this combination, RPA revealed a significantly (P < 0.01 ) higher rate of correct reclassification in 89% of patients with 89.3% sensitivity and 88% specificity for obstruction [AUC: 0.96]. Conclusion . NIRS data can be of diagnostic value for BOO in men with LUTS.